Determinants of organisational agility in a South African commercial cleaning company - Mguni, Charity (My University, 2017)
Organisations today operate in a dynamic environment where there are high levels of competition, shifting customer preferences, globalisation and rapid technology development (Alhadid & Abu-Rumman, 2015). The complexity, volatility and unpredictability of the business environment today has led to the failure of many organisations (Tseng & Lin, 2011). Today’s organisations are tasked with not only responding to rapid changes in their environments (PWC, 2015), but also with the reality of constantly re-aligning their organisations with this ever-changing context (Nijssen & Paauwe, 2012). The South African commercial cleaning industry is no different; the industry has continuously been evolving, with new players and new products disrupting the market by providing more efficient ways of cleaning at more affordable prices. The challenge of adapting to unforeseen changes has led to the evolution of one of the latest concepts in business strategies, referred to as agility. Organisational agility refers to an organisation’s ability to rapidly and efficiently adjust to any unexpected or sudden changes in its environment (Ganguly, Nilchiani, & Farr, 2009). The key objective of this study was to provide a better understanding of the concept of organisational agility by identifying its determinants. Using a qualitative research method, specifically a single-site case study approach, the research set out to identify the internal determinants of organisational agility based on the perspective of Bidvest Prestige Cleaning Solutions’ management team. Twelve semi-structured interviews were conducted and the themes that emerged from the interviews validated and supported the findings from the literature review. The literature review identified adaptable organisation designs, agile and adaptive workforce, adoption of technology, and fast organisational learning as key determinants of organisational agility. The research results also identified three of these factors but did not identify adaptable organisation designs as one of the factors that affected a company’s ability to be agile. However, when the respondents were asked if the structure of the organisation affected its ability to be agile, they were unanimous that the structure of the organisation did indeed determine whether it is responsive and adaptable to change.
MBA(Thesis)
Keywords: Organizational learning -- South Africa. Building cleaning industry -- South Africa -- Management.